2012
DOI: 10.1017/s0950268812001628
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the vaccination efficacy against H5N1 in domestic poultry in the Red River Delta in Vietnam

Abstract: SUMMARYThe domestic poultry population in Vietnam has been vaccinated against highly pathogenic avian influenza (HPAI) H5N1 since 2005. Since then, outbreaks have continued to occur without a clear understanding of the mechanisms involved. The general objective of this study was to understand the epidemiology of the disease in the context of vaccination and to draw some conclusions about vaccination efficacy in the domestic poultry population of the Red River Delta area. Five cross-sectional surveys to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
(54 reference statements)
4
14
0
Order By: Relevance
“…This is consistent with findings from previous studies which showed that the risk of HPAI H5N1 increased with flock size (Desvaux et al, 2012). This may be due to an increased transmission in large flocks, related to higher poultry density and higher degree of contacts between birds.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with findings from previous studies which showed that the risk of HPAI H5N1 increased with flock size (Desvaux et al, 2012). This may be due to an increased transmission in large flocks, related to higher poultry density and higher degree of contacts between birds.…”
Section: Discussionsupporting
confidence: 93%
“…In spite of these limitations, the present study made it possible to identify risk factors associated with exposure of poultry to AIV. The study found higher AIV seroprevalence in palmipeds (ducks and geese) than in chickens, which is consistent with findings by other serological surveys carried out in unvaccinated birds raised in small-scale farms of Indonesia (Santhia et al, 2009) or Vietnam (Henning et al, 2009;Desvaux et al, 2012). The reason why this should be so can be explained.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These studies show that use of vaccines that are antigenically distant to the circulating strains led to lack of protection due to low HI titres against the challenge strains. Upon closer examination however, it can be seen (where the data are available) that even HI titres against the vaccine strains were low in these vaccination programmes, thus indicating that the vaccine had failed to induce immunity to begin with [20,37,38]. In addition, reports from the field have emerged in which it is shown that in some cases where vaccination against HPAI is applied nationwide, the population coverage is extremely low, thus allowing transmission to take place in a seemingly vaccinated population [12,14,20].…”
Section: Discussionmentioning
confidence: 99%
“…Prevention measures aimed at reducing the intensity of AIV transmission should be focused on these areas. Successful vaccination programs may be difficult to sustain in the long-term and should be complemented by other control measures (Desvaux et al 2013). Our synthesis highlights the importance of free-grazing duck farming in increasing risks at the wild-domestic interface.…”
Section: Discussionmentioning
confidence: 99%